Mapping the research landscape: energy storage of bio-nanoparticle-enhanced phase change materials for solar desalination—a scientometric framework - Sathwika, Balusu; Kavitha, A.; Alasiri, Abdulaziz; Sivakumar, Soubraylu; Jathar, Laxmikant; Rao, M. C.; Koteswara Rao, K.; Nagaraj, J.; Selvaraju, P.; Omara, Zakaria; Shanmugan, S. (Frontiers in Water, 2025)
Solar desalination is an economical and eco-friendly approach to producing potable water, particularly in remote areas. Nevertheless, the limited efficiency of traditional solar panels restricts their ability to fulfill the growing demand for clean water. This study focuses on improving the performance of single-basin solar stills (SBS) by incorporating paraffin wax as a phase change material (PCM) with copper nanoparticles (Cu NPs) and agro-based materials in a stepped design. A scientometric analysis framework was applied to map the research landscape, followed by an experimental evaluation in which SBS units were fabricated and tested under controlled solar exposure with varying combinations of PCM, Cu NPs, and concentrators. The research is tailored to accommodate diverse climatic and operational conditions. Results reveal that the combination of PCM and Cu NPs significantly enhances freshwater output compared to traditional setups. The modified SBS demonstrated a productivity improvement of 67.18% for single-effect and 125% for double-effect configurations. The use of PCM alone resulted in a 21.5% boost in productivity, while the SBS design excluding CuO-based nanofluids achieved approximately 32% higher freshwater generation by utilizing solar energy. Moreover, combining a concentrator with PCM led to an additional 26% increase in efficiency. These results highlight the potential of integrating PCM and nanoparticles as an effective strategy to optimize SBS performance for sustainable water desalination.